Medical genetics and its implementation in speech, language and hearing disorders - Trajkovski, Vladimir (My University, 2015)
It is critical that speech language pathologists and audiologists understand principles of medical genetics, genetic testing and genetic counseling. Vocal communication mediated by speech and language is a uniquely human trait, and has served an important role in the development of our hearing. Scientists are beginning to uncover the neurogenetic pathways that underlie our unparalleled capacity for spoken language. The purpose of this article is to review recent findings suggesting a genetic susceptibility for speech, language and hearing disorders. Deficits in speech and language functions can be: aphasia, stuttering, articulation disorders, verbal dyspraxia, and dyslexia. A number of these disorders have been shown to cluster in families, suggesting that genetic factors are involved, but their molecular etiology is not well known. Linkage studies and molecular genetic analyses in a large family containing multiple individuals affected with verbal dyspraxia led to the discovery of mutations in the FOXP2 gene. In studies of stuttering, linkage and candidate gene approaches in consanguineous families identified mutations in the lysosomal enzyme-targeting pathway genes GNPTAB, GNPTG, and NAGPA, revealing a role for inherited defects in cell metabolism in this disorder. Sixty percentages of congenital deafness has a primary genetic etiology. Complete medical genetics evaluation in a young child with a significant hearing loss has a high diagnostic yield. A specific etiology can be identified in close to 90% of the cases. Two known causes of early childhood hearing loss – congenital CMV and connexin 26 mutations - each account for about 40% of the identified children. Knowledge of genetic factors may improve diagnosis and early identification of children at risk of speech, language and hearing disorders. This early identification will allow for timely environmental intervention. Early intervention is crucial because of the potential of communication disorders to lead to social and educational isolation.
Keywords: medical genetics, speech disorders, language impairments, hearing disorders